2011
DOI: 10.1007/s00404-011-1927-5
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous uterine rupture at the 21st week of gestation caused by placenta percreta

Abstract: In a pregnant woman with severe abdominal pain even in the 21st week of gestation a placenta percreta has to be considered as a differential diagnosis. If there is no evidence of other causes, laparoscopy may help to confirm the diagnosis and hysterectomy is a life saving intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…Overall, women with accreta placentation should be cared for according to the risks of severe maternal bleeding and premature delivery. Placenta percreta can be associated with major prenatal complications from early in pregnancy, such as uterine rupture [150][151][152] and bladder involvement with associated life-threatening haemorrhage. [153][154][155] A 2015 expert review has suggested that caesarean delivery of women at high risk and/or diagnosed prenatally with placenta accreta spectrum, in particular its invasive forms, should occur in a specialist centre with multidisciplinary expertise and experience in managing complex pelvic surgery, and with access to an adult intensive care unit and NICU.…”
Section: [New 2018]mentioning
confidence: 99%
“…Overall, women with accreta placentation should be cared for according to the risks of severe maternal bleeding and premature delivery. Placenta percreta can be associated with major prenatal complications from early in pregnancy, such as uterine rupture [150][151][152] and bladder involvement with associated life-threatening haemorrhage. [153][154][155] A 2015 expert review has suggested that caesarean delivery of women at high risk and/or diagnosed prenatally with placenta accreta spectrum, in particular its invasive forms, should occur in a specialist centre with multidisciplinary expertise and experience in managing complex pelvic surgery, and with access to an adult intensive care unit and NICU.…”
Section: [New 2018]mentioning
confidence: 99%
“…Spontaneous preterm uterine rupture is very rare [1,2,4,5,[13][14][15][16]. In vitro fertilization (IVF) is known to raise the risk of cornual pregnancy and placenta anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…6 Rupture uterus in women with adherent placenta has been reported by various authors at 14, 18, 21 weeks. [6][7][8] All these women had risk factors for placental adherence including previous hysterotomy and previous curettages.…”
Section: Discussionmentioning
confidence: 99%